2008
DOI: 10.1080/08910600802408111
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility of bacterial isolates from probiotic products available in Italy

Abstract: Objective: An emerging issue of probiotic products is the antibiotic resistance of the strains used. The aim of this study was to determine the susceptibility of the isolates of 10 probiotic products available in Italy. Materials and methods: The susceptibility of 15 strains of Lactobacillus spp., 5 Streptococcus salivarius ssp. thermophilus, 1 Enterococcus faecium and 8 Bifidobacterium spp. to several groups of antibacterial agents was determined by E-test using MRS agar for Lactobacillus spp. and E. faecium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…These organisms have the potential to act as reservoir of antimicrobial resistant genes and which have potential to be transferred to other bacteria. Moreover, intrinsic resistance to vancomycin was confirmed for L. paracasei, L. salivarius and L. plantarum, and L. salivarius was also typically resistant to erythromycin [ 31 ]. In other study, L. salivarius had the highest resistance to kanamycin and neomycin, but demonstrated the lowest resistance to penicillin [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…These organisms have the potential to act as reservoir of antimicrobial resistant genes and which have potential to be transferred to other bacteria. Moreover, intrinsic resistance to vancomycin was confirmed for L. paracasei, L. salivarius and L. plantarum, and L. salivarius was also typically resistant to erythromycin [ 31 ]. In other study, L. salivarius had the highest resistance to kanamycin and neomycin, but demonstrated the lowest resistance to penicillin [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial susceptibility patterns for L. salivarius isolated from multiple sources have been reported, however scarcely. For example, Blandino et al (2008) studied the AMR profiles of LAB isolated from probiotic products in Italy and found that one strain of L. salivarius was atypically resistant to erythromycin. The authors indicated that this was a nonintrinsic case of resistance, compared to the resistance level of other LAB in the study (Blandino et al 2008).…”
Section: Antimicrobial Resistance Of L Salivariusmentioning
confidence: 99%
“…For example, Blandino et al (2008) studied the AMR profiles of LAB isolated from probiotic products in Italy and found that one strain of L. salivarius was atypically resistant to erythromycin. The authors indicated that this was a nonintrinsic case of resistance, compared to the resistance level of other LAB in the study (Blandino et al 2008). Conversely, Langa et al (2012) reported that L. salivarius CECT 5713 isolated from human milk was sensitive to most antibiotics tested and no transmissible genes potentially involved in antibiotic resistance were detected (Langa et al 2012).…”
Section: Antimicrobial Resistance Of L Salivariusmentioning
confidence: 99%
“…In a few species, the locus is only composed of the TCS predicted operon. The first and the third configurations are observed in vancomycin-resistant Lactobacillus species (Mackey et al, 1993;Wilks et al, 2004;Klare et al, 2007;Balandino et al, 2008) except for L. fermentum which displays a variable strain-dependent vancomycin resistance (Rossetti et al, 2009). The second configuration is only observed in the vancomycinsusceptible species.…”
Section: Predictive Analysis Of Operon Cwars-ldca and Polar Effect Ofmentioning
confidence: 96%